The Effect of Family History of Seizures as A Risk Factor for The Inci-dence of Recurrent Febrile Seizures and Types of Febrile Seizures in Children at Waled Cirebon Hospital - Permana, Irman; Meyrisa, Nissa Suci; Brajadenta, Gara Samara (Eduvest - Journal of Universal Studies, 2025)
Febrile seizures (FS) are common in children aged 6 months to 5 years, with familial seizure history implicated as a risk factor. However, regional data gaps persist, particularly in Indonesia. The research aims to analyze the influence of family seizure history on FS recurrence and types at Waled Hospital, Cirebon. A retrospective cohort study of 66 pediatric FS patients (2022) used chi-square tests and Prevalence Ratio (PR) analysis. Children with familial seizure history had significantly higher recurrent FS rates (62.1%, PR = 2.297, *p* = 0.009) but no association with seizure type (65.5% simple FS, PR = 0.797, *p* = 0.639). Familial history is a critical predictor of FS recurrence but not seizure complexity, underscoring the need for targeted monitoring and genetic-environmental interaction studies in high-risk children. This study contributes localized insights to global FS research and informs clinical prevention strategies.